Inovasi U-Jabar untuk Pemahaman Konsep Operasi pada Bentuk Aljabar - Iis Sonia (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
U-JABAR is an algebra tile designed to help students understand the concept of algebraic forms and perform addition and subtraction operations of algebraic expressions. This tool is used in teaching algebra material for Grade VII, as students often face difficulties in understanding abstract algebraic forms and are introduced to symbolic variables for the first time. U-JABAR is made from colored acrylic material, positive-negative stickers, a game board, and question cards. Results from testing the tool on students showed an improvement in learning outcomes for 31 students, with the average score increasing from a pretest score of 58.70 to a posttest score of 80.32, and the number of students meeting the minimum competency standard (KKM) rising from 13 to 26 students. Therefore, this tool can effectively help improve student learning outcomes.